The Role of Technical and Vocational Training for Entrepreneurship Development and Business Skills in the Boushehr Province Technical and Vocational Training IRAN Aspect. - Behroozi, Mohamad (Universitas Ahmad Dahlan, 2017)
AbstractÂ This study was to identify the role of technical and vocational training in entrepreneurship development and business skills in the main office of B. province technical and vocational training. The corelational study was conducted. The population consisted of 1500 apprentices among which 420 persons were randomly selected according to Cochran formula based on a systematic sampling method. Data is gathered via a researcher-structured questionnaire containing 35 items based on Likert scale. Content validity and CronbachâS Alpha (Î±=/94) are used. The data was analysed using SPSS software. The descriptive and inferential statistics are also used to examined the hypotheses.Â TheÂ result showed that there was a significant relationship between technical and vocational training and dimensions of entrepreneurship in the apprentices that includes: technical and vocational training, knowledge and technical ability, success seeking.Â Key Words: entrepreneurship, creativity, business skills, technical and vocational training